2006
DOI: 10.1364/oe.14.005301
|View full text |Cite
|
Sign up to set email alerts
|

Experiment observation of self-mixing interference in distributed feedback laser

Abstract: The experiment observation of self-mixing interference in distributed feedback (DFB) laser has been illuminated in this paper. The influences on self-mixing interference have been discussed in both simulation and experiment through changing the conditions of external cavity. The experiment results show a good agreement with the simulation results, and validate the feasibility of DFB lasers for self-mixing interference application. Combining the self-mixing interference technique and DFB laser, we can obtain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…The solid and dashed lines and the solid point refer to output variations at the case of a ¼ 2, 6, and 10, respectively. The inclination degree of the waveform becomes stronger as a increases, and the MDOV increases appreciably which could not be found in DFB lasers [6]. …”
Section: Numerical Analysismentioning
confidence: 70%
See 1 more Smart Citation
“…The solid and dashed lines and the solid point refer to output variations at the case of a ¼ 2, 6, and 10, respectively. The inclination degree of the waveform becomes stronger as a increases, and the MDOV increases appreciably which could not be found in DFB lasers [6]. …”
Section: Numerical Analysismentioning
confidence: 70%
“…In previous research, many researchers analyzed the theory and observed the experimental phenomena of the self-mixing interference in lasers, which focused on the laser diode [1], the vertical-cavity surface-emitting laser [2], the Nd:YAG laser [3], the CO 2 laser [4], and the distributed feedback laser (DFB) laser [5,6]. In this paper, we focused on three-section distributed Bragg reflector (DBR) lasers.…”
Section: Introductionmentioning
confidence: 99%
“…For a sinusoidal interference pattern, there will again be a second derivative-like structure in the second harmonic signal, which also takes the form of a sinusoidal modulation. The amplitude of the fringes in the 2f signal depends on the amplitude of the intensity modulation in the direct signal as described by (3), (4) or (5), but also on the ratio of the laser wavelength modulation to the free spectral range of the interference fringes Δλ [13] . For λ m <<Δλ, the result as we sweep in wavelength is approximately equal to the second derivative of the underlying spectrum.…”
Section: Effect Of Wavelength Modulation Spectroscopymentioning
confidence: 99%
“…This modulation can be monitored on the output from the rear facet, using the monitor photodiode which is often found in the laser diode package. A typical set-up involves the use of a single-mode Fabry-Perot laser diode, but self-mixing interference has been demonstrated using both distributed feedback (DFB) laser diodes [5] and vertical cavity surface emitting lasers (VCSELs) [6] . Self-mixing interference has been observed using mirrors as targets and from rough surfaces, where the returned light takes the form of a speckle field [7] .…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, many researchers analyzed the theory and observed the experiment phenomena of optical feedback effect focused on the laser diode. Along with further development of optical feedback effect theory and the research of a passel of new type medium, more and more researchers consider using new type lasers -the vertical-cavity surface-emitting laser (VCSEL) [15], the Yb: Er glass laser [16], the CO 2 laser [17], the distributed feedback (DFB) laser [18], etc. -for sensing applications which are based on optical feedback effect, looking forward to obtaining better performance.…”
Section: Introductionmentioning
confidence: 99%